Enrichment of indigenous pre-primary education of Bangladesh through HCI - Azhar, Tawsif; Karmakar, Sowmik Shovon; Jannat, Fiona-E; Hossain, S. M. Bayazid (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.